UNIVERSITY STUDENTS’ PERCEPTION IN LEARNING VOCABULARY THROUGH DUOLINGO - Renilza Nurhisyam; Sriati Usman; Agussatriana Agussatriana; Rofiqoh Rofiqoh (Tadulako University, 2022)
The objective of this research was to identify university students’ perception in learning vocabulary through Duolingo. The researchers applied qualitative descriptive by using questionnaire and interview questions in collecting data. The subjects were 10 students of English Education Study Program of Tadulako University batch 2021 who were currently using or have ever used Duolingo. There were 10 questions in the questionnaire and six questions in the interview questions. The results indicate that students’ perception in learning vocabulary through Duolingo is dominantly positive with the average score of 89.76%. The results of the research proved that Duolingo is very helpful in learning vocabulary since the application is easy to be used, interesting, fun, and free without ads. However, Duolingo requires an internet connection to access the material.